Tourism Color Run Party Event Management in Ngawi - Nurmala Fadin, Delfian Intan (Ann Publisher, 2024)
With every city, big or small, hosting a steady schedule of fresh events each year, events or festivals have become an integral element of Indonesian culture. A prime example is Ngawi City, East Java's Color Run Party. Even then, this event brings up several concerns, including the buildup of trash and the degradation of Indonesian culture due to the absence of regional components. The impact of the Color Run Party on society and culture, as well as destination and visitor management, are covered in this article. A qualitative technique is employed as the primary instrument in this research method, which describes the object's natural state. Findings indicate that although destination management and other event-related factors have been well-organized, some areas, such as trash management and the absence of regional cultural components, still need improvement. So that this event not only concentrates on quantity but also considers the effects on the environment and culture, more cautious management is required. Keywords: local culture, tourism destination management, Color Run Party, festival, and event management.